State of the Art of Different Zirconia Materials and Their Indications According to Evidence-Based Clinical Performance: A Narrative Review - Alexia María Arellano Moncayo; Lissethe Peñate; María Arregui; Luis Giner-Tarrida; Rosario Cedeño (MDPI AG, 2023)
The aim of this study was to perform a narrative review to identify the modifications applied to the chemical structure of third- and fourth-generation zirconia ceramics and to determine the influence of these changes on the mechanical and optical properties. A bibliographical search using relevant keywords was conducted in the PubMed® and EBSCO databases. The abstracts and full texts of the resulting articles were reviewed for final inclusion. Fifty-four articles were included in this review. The analyzed topics were: (1) the composition of first- and second-generation zirconia materials (Y-TZP), (2) the behavior of the studied generations in relation to mechanical and optical properties, and (3) the modifications that were carried out on third-generation (5Y-TZP) and fourth-generation (4Y-TZP) zirconia materials. However, studies focusing on these specific characteristics in third- and fourth-generation zirconia materials are scarce. The review shows that there is a lack of sufficient knowledge about the chemical modifications of zirconia in the new generations.